2018
DOI: 10.1259/bjr.20180160
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of bladder volumes based on treatment planning CT and BladderScan® BVI 6100 ultrasound device in a prostate radiation therapy population

Abstract: The BladderScan® BVI 6100 provides a convenient and non-irradiating method of indicating BV for use in prostate RT patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…The estimated glomerular ltration rate (eGFR) was estimated by the following conversion formula for Japanese men: eGFR (mL/min/1.73 m 2 ) = 194 × serum creatinine (SCr) −1.094 × age − 0.287 (10). For the post-void residual urine volume, the urine volume in the bladder immediately after urination was three-dimensionally measured with an ultrasonic diagnostic apparatus (Bladder Scan BVI 3000 or BVI 6100; Sysmex, Kobe, Japan) (11,12). Patient age was the age at the time of planning CT.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…The estimated glomerular ltration rate (eGFR) was estimated by the following conversion formula for Japanese men: eGFR (mL/min/1.73 m 2 ) = 194 × serum creatinine (SCr) −1.094 × age − 0.287 (10). For the post-void residual urine volume, the urine volume in the bladder immediately after urination was three-dimensionally measured with an ultrasonic diagnostic apparatus (Bladder Scan BVI 3000 or BVI 6100; Sysmex, Kobe, Japan) (11,12). Patient age was the age at the time of planning CT.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Many of the studies included in this review, however, did not specify the exact drinking protocol, which limited definition of the optimal bladder volume/drinking protocol. In a retrospective cohort study of 1080 patients treated with 3D-CRT to the prostate, use of both an empty rectum and comfortably full bladder was associated with reduced biochemical and clinical relapse and risk of dying from prostate cancer [40]. However, some full bladder protocols used for prostate radiotherapy have been shown to result in greater inter-fraction variation in prostate position compared to empty bladder protocols, especially in the superior and anterior directions, and therefore may be less reproducible [41].…”
Section: Bladder Filling Protocolsmentioning
confidence: 99%
“…42 Studies of ultrasound bladder scanning have reported improved consistency of bladder volume during prostate radiotherapy. [43][44][45] This might be because measuring bladder volume encourages better patient compliance with drinking protocols. 43 A cohort study of 190 patients by Mullaney et al found that bladder volume measured by ultrasound was strongly positively correlated with the bladder volume delineated on the radiotherapy planning CT scan.…”
Section: Rectal Spacersmentioning
confidence: 99%
See 2 more Smart Citations